Pengaruh Pendapatan Asli Daerah (PAD), Dana Alokasi Umum (DAU) Dan Dana Alokasi Khusus (DAK) Terhadap Kinerja Keuangan Daerah Serta Dampaknya Pada Keterlambatan Penyerapan Anggaran Di Kabupaten Minahasa Selatan - Yuliana Heydemans; Agnes L.Ch.P. Lagian; Een.N.Walewangko (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research analyzes the influence of Regional Original Income (PAD), General Allocation Funds (DAU), and Special Allocation Funds (DAK) on regional financial performance as well as their impact on delays in budget absorption in South Minahasa Regency. Using a quantitative approach, this research explores the relationship between the main regional income sources, the effectiveness of financial management, and the optimization of budget absorption. The research results show that PAD, DAU, and DAK have a significant influence on regional financial performance. Furthermore, regional financial performance is proven to mediate the relationship between sources of income and delays in budget absorption. Low performance in regional financial management is one of the main causes of delays in implementing development programs. Practical recommendations are provided to increase the efficiency of PAD management, optimize DAU and DAK allocations, and strengthen regional financial management systems to accelerate budget absorption and support sustainable regional development.